Dynamic Model of a Drilling Rig with a Top Drive System for Rotary Steerable Systems - Ashcheulov, Aleksandr; Nikitin, Sergey (International Journal of Engineering and Technology, 2018)
The fundamentals and principles of constructing a generalized dynamic model of a drilling rig with a top drive system for rotary steerable systems, which consists of models of individual mechanisms and takes into account many physical processes occurring in a real object, are presented. The most complex element of such a system is the drill string model, which has many degrees of freedom.Â